2020
DOI: 10.1097/rct.0000000000001005
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Arterial Phase on the Detection of Cervical Lymph Node Metastasis From Papillary Thyroid Carcinoma: A Quantitative Evaluation on Multiphasic Computed Tomography

Abstract: Objective The purpose of this study was to assess the diagnostic performance of multiphasic computed tomography (CT) in the discrimination of metastatic lymph nodes (LNs) of papillary thyroid cancer by using quantitative parameters. Methods This study enrolled 272 pathologically proven metastatic and benign LNs. Multiphasic CT was utilized by using nonenhanced, arterial (25-second delay), and venous (80-second delay) phases. Mean tissue attenuation valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…This effect has been observed in normal sternal lymph nodes of dogs, where attenuation values increased significantly between precontrast and postcontrast images 20 . In a recent study of cervical lymph nodes in humans with thyroid cancer, a cutoff value of 109 HU in the arterial phase (25 s after contrast medium injection) yielded high sensitivity of 93.4% and specificity of 99.3% for the detection of metastasis 24 . In our cases, the median absolute density value 1 min after injection was significantly higher in positive SLNs than in normal ones, providing good accuracy (AUC 0.846) with a threshold value of 48.3 HU in the periphery of the lymph node.…”
Section: Discussionmentioning
confidence: 77%
“…This effect has been observed in normal sternal lymph nodes of dogs, where attenuation values increased significantly between precontrast and postcontrast images 20 . In a recent study of cervical lymph nodes in humans with thyroid cancer, a cutoff value of 109 HU in the arterial phase (25 s after contrast medium injection) yielded high sensitivity of 93.4% and specificity of 99.3% for the detection of metastasis 24 . In our cases, the median absolute density value 1 min after injection was significantly higher in positive SLNs than in normal ones, providing good accuracy (AUC 0.846) with a threshold value of 48.3 HU in the periphery of the lymph node.…”
Section: Discussionmentioning
confidence: 77%
“…Gürsoy et al. ( 17 ) studied 272 LNs in 43 patients, and the results showed that the sensitivity and specificity were, respectively, 93.4% and 99.3%, with the cutoff value of EN HU 109 HU. Su et al.…”
Section: Discussionmentioning
confidence: 99%
“…( 16 ) and Gürsoy et al. ( 17 ) included the possible deviation of sample representativeness (too many LNs were selected in one patient) and the fact that the LNs did not reach or completely reach the level of comparison between pathology and imaging. The small sample size was the limitation of the study by Su et al.…”
Section: Discussionmentioning
confidence: 99%
“…The CT value of the carotid artery (CT‐a) in the same venous slice was measured as a reference, and the absolute enhancement CT value (ΔCT) was calculated by ΔCT = CT‐v − CT‐u 27 . The normalized enhancement CT value (NCT) was calculated by NCT = CT‐v/CT‐a 28 . 2) Enhancement homogeneity was classified as homogeneous or inhomogeneous (Figure 2, A and B).…”
Section: Methodsmentioning
confidence: 99%